Metode Drill Berbasis Aplikasi Kahoot terhadap Hasil Belajar Siswa Materi Operasi Bilangan Bulat untuk Kelas VII SMP Muhammadiyah 4 Palembang - Syaifudin, Syaifudin; Antari, Luvi; Andhika, Muhammad Reza (Universitas Muhammadiyah Palembang, 2021)
This type of research is experimental research. The population in this study were all seventh grade students of SMP Muhammadiyah 4 Palembang in the academic year 2021/2022 with a sample of class VII U3 as the experimental class and VII U2 as the control class. After learning using the drill method based on the Kahoot application, the average value is and the standard deviation is S1=14,8165. While learning using the drill method without the Kahoot application, the average value is and the standard deviation is . Based on the criteria for testing the hypothesis, the value of and means that is in the rejection area of Ho, which means Ha is accepted. Thus the hypothesis which states